Effects of stainless-steel tank and ceramic tank on the quality and microorganisms of fermented chilli - ZHONG Qiu, CHEN Xiaolong, LIN Hongbin, XING Yage, LI Meng, ZHANG Chengyi, LI Shengshuai, RAO Yu (Zhongguo niangzao)
Chilli was fermented using stainless-steel tank and ceramic tank as containers. The quality characteristics and microbial changes of fermented chilli were explored through analyzing physicochemical properties, lactic acid bacteria count, etc. The results indicated that the pH value of the stainless-steel tank group (ST group) first decreased to 4.0 than the ceramic tank group (CK group) during the fermentation process. After 12 d of fermentation, the lactic acid content (3.65 g/L) and total acid content (4.61 g/kg) of the ST group were significantly higher than those of the CK group (3.11 g/L, 3.60 g/kg) (P<0.05). During the fermentation process, the nitrite peak in the ST group was earlier than that in the CK group, and the nitrite content in both groups was less than 0.89 mg/kg after 12 d. There was no significant difference in hardness and chewability between the two groups after fermentation (P>0.05). The number of lactic acid bacteria in the ST group showed a stable increase during the fermentation process, reaching a peak of 7.55 lg (CFU/ml), which was higher than the CK group [7.11 lg (CFU/ml)]. The results of electronic nose analysis showed that the response values of nitrogen oxides and alcohol, some aromatic compounds in the ST group during the fermentation process were significantly higher than those of the CK group (P<0.05). The study indicated that it was feasible to ferment Paocai in stainless-steel tank, which could improve the quality of Paocai and replace traditional ceramic tank fermented Paocai in industrial production in the future.